A Novel T55A Variant of Gsα Associated with Impaired cAMP Production, Bone Fragility, and Osteolysis - Kelly Wentworth; Alyssa Hsing; Ashley Urrutia; Yan Zhu; Andrew E. Horvai; Murat Bastepe; Edward C. Hsiao (Case Reports in Endocrinology)
G-protein coupled receptors (GPCRs) mediate a wide spectrum of biological activities. The GNAS complex locus encodes the stimulatory alpha subunit of the guanine nucleotide binding protein (Gsα) and regulates production of the second messenger cyclic AMP (cAMP). Loss-of-function GNAS mutations classically lead to Albright’s Hereditary Osteodystrophy (AHO) and pseudohypoparathyroidism, often with significant effects on bone formation and mineral metabolism. We present the case of a child who exhibits clinical features of osteolysis, multiple childhood fractures, and neonatal SIADH. Exome sequencing revealed a novel de novo heterozygous missense mutation of GNAS (c.163A<G, p.T55A) affecting the p-loop of the catalytic Gsα GTPase domain. In order to further assess whether this unique mutation resulted in a gain or loss of function of Gsα, we introduced the mutation into a rat GNAS plasmid and performed functional studies to assess the level of cAMP activity associated with this mutation. We identified a 64% decrease in isoproterenol-induced cAMP production in vitro, compared to wild type, consistent with loss of Gsα activity. Despite a significant decrease in isoproterenol-induced cAMP production in vitro, this mutation did not produce a classical AHO phenotype in our patient; however, it may account for her presentation with childhood fractures and osteolysis.